The Cannabis Effects Expectancy Questionnaire-Medical (CEEQ-M): Preliminary psychometric properties and longitudinal validation within a clinical trial - Weiss, Jakob H; Tervo-Clemmens, Brenden; Potter, Kevin W; Evins, A Eden; Gilman, Jodi M (Psychological assessment, 2023)
The use of cannabis for medical symptoms is increasing despite limited evidence for its efficacy. Expectancies-prior beliefs about a substance or medicine-can modulate use patterns and effects of medicines on target symptoms. To our knowledge, cannabis expectancies have not been studied for their predictive value for symptom relief. The 21-item Cannabis Effects Expectancy Questionnaire-Medical (CEEQ-M) is the first longitudinally validated measure of expectancies for cannabis used for medical symptoms. The questionnaire was developed for a randomized clinical trial of the effect of state cannabis registration (SCR) card ownership on symptoms of pain, insomnia, anxiety, and depression in adults ( = 269 across six questionnaire administrations). Item-level analyses ( = 188) demonstrated between-person stability of expectancies and no aggregate, within-person expectancy changes 3 months after individuals gained access to SCR cards. Exploratory factor analysis ( = 269) indicated a two-factor structure. Confirmatory factor analysis at a later timepoint ( = 193) demonstrated good fit and scalar invariance of the measurement model. Cross-lagged panel models across 3 and 12 months ( = 187 and 161, respectively) indicated that CEEQ-M-measured expectancies did not predict changes in self-reported cannabis use; symptoms of pain, insomnia, anxiety, and depression; and well-being. However, greater baseline cannabis use predicted more positive expectancy changes. The findings suggest that the CEEQ-M is psychometrically sound. Future work should clarify at what timescales cannabis expectancies have predictive value and how cannabis expectancies for medical symptoms are maintained and diverge from other substance use expectancies. (PsycInfo Database Record (c) 2023 APA, all rights reserved).